2002
DOI: 10.1271/bbb.66.65
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Increases in Safflower and Cucumber Seedlings Exposed to Strong Visible Light with Limited Water

Abstract: Abbreviations : UV, ultraviolet; HPLC, high-pressure liquid chromatography; Chl, chlorophyll; fresh W dry ratios, the ratios of the fresh weights to dry weights; DMSO, dimethyl sulfoxide Biosci. Biotechnol. Biochem., 66 (1), [65][66][67][68][69][70][71][72] 2002 To assess eŠects of the environmental stress on polyphenol compounds (polyphenols) in plants, the polyphenol contents were investigated in the seedlings of saOEower (Carthamus tinctrius L.) and cucumber (Cucumis sativus L.) grown under three types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…Given the close correlation of shoot growth (as influenced by SWC) and WSI to total polyphenols, these results suggest an association of plant polyphenols with water stress in tea. This observation agrees with results of Yaginum et al 25) who noted increased polyphenols in light and water-stress resistant safflower and cucumber seedlings as compared to those which responded weakly to the stresses. Further investigation of flavonoid contents in safflower revealed that a strong antioxidant was responsive to both light and water stress while a weak antioxidant remained unchanged.…”
Section: Discussionsupporting
confidence: 93%
“…Given the close correlation of shoot growth (as influenced by SWC) and WSI to total polyphenols, these results suggest an association of plant polyphenols with water stress in tea. This observation agrees with results of Yaginum et al 25) who noted increased polyphenols in light and water-stress resistant safflower and cucumber seedlings as compared to those which responded weakly to the stresses. Further investigation of flavonoid contents in safflower revealed that a strong antioxidant was responsive to both light and water stress while a weak antioxidant remained unchanged.…”
Section: Discussionsupporting
confidence: 93%
“…the experimental period, the fresh W dry ratio of the leaves was reduced by the stress. It was ascertained in this study as well as in our previous study, 8) that the light W water stress condition in these experiments caused no severe growth inhibition. Figure 2 shows the time-dependent changes of polyphenol contents in the cotyledons (a) and the foliage leaves (b).…”
Section: Resultssupporting
confidence: 74%
“…The germination and cultivation procedures were performed according to the method described in our previous report. 8) After germinating in the dark for 48 h, the seedlings were pre-cultivated with a 12-h light (5000 lux) and 12-h dark cycle at 259 C for 7 days and then transferred for main cultivation under the following conditions: Control condition, the light intensity was 6000 lux and a total of 170 ml of water per day was supplied 2 or 3 times daily; Light W water stress condition, the light intensity was 45,000 lux and a total of 100 ml of water per day was supplied. Five seedlings were harvested every 3 days after germination, and a pair of cotyledons and two foliage leaves from the lowest position of each seedling were sampled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported that the presence and increase of flavonoids in plants may be associated with several abiotic factors including UVB, temperature and drought among others, such as environmental stress. 40,41 In line with this, Guidi et al 42 studied the interactions of water stress and solar irradiance on the physiology and biochemistry with special emphasis on flavonoid production of Ligustrum vulgare. They observed that the content of quercetin and luteolin derivatives increased in response to full sunlight irrespective of the water treatment; however, the phenylpropanoid concentrations increased in response to water stress only in shaded leaves.…”
Section: Resultsmentioning
confidence: 96%